Suitability evaluation of remediation technology for polluted farmland - Li, Yang; Pan, Ligang; Li, An; Wang, Beihong (International Journal of Agricultural and Biological Engineering, 2015)
The suitability evaluation model of the remediation technology of polluted farmland has been constructed by analytic hierarchy process. The evaluation index of remediation technology has been constructed based on the physical and chemical index of farmland, farming system and the characteristic of remediation technology. In addition, the potential risk factors such as the distance of the industrial and mining enterprises, and the economy factors such as repair cost and local economy level have all been considered to construct the suitability evaluation system of the remediation technology of polluted farmland. Shilou town in Beijing was selected for the testing site, with the pollution of cadmium, arsenic and organic matter pollution. Chemical passivation, phytoremediation and biological compost technology were used for restoring the polluted farmland. According to the suitability evaluation model, the phytoremediation technology is suitable for general pollution. And chemical passivation and biological compost technology are more suitable to restore the polluted farmland. The combined remediation technologies of chemical passivation and phytoremediation are more suitable. It can avoid the limit of the one technology, complement the defect for each other and receive more remediation effects.Keywords: polluted farmland, remediation technology, suitability evaluation, analytic hierarchy process (AHP)DOI: 10.3965/j.ijabe.20150802.1024